Creative disruption: Edward Bunker, carceral habitus, and the criminological value of fiction - Page, Joshua (Theoretical criminology, 2020)
Drawing on Edward Bunker’s semi-autobiographical novels, this article argues for the criminological value of fiction. Drawing inspiration and extending core insights from “narrative criminology” and “popular criminology”, we posit that novels and other creative sources can disrupt scholarly commonsense, pushing scholars to reconsider and extend theoretical perspectives. Specifically, Bunker’s fiction encourages re-thinking of overly cognitive (i.e. “mentalist”) understandings of “prisonization”, which do not sufficiently capture the embodiment of carceral culture and routines. Through Bunker’s work, we flesh out the concept of “carceral habitus”—itself deeply gendered and raced—to extend theories of prisonization, deepening understandings of how incarceration transforms people. We affirm that literary devices provide scholars innovative paths to communicating full-bodied accounts that breathe new vitality into criminological theory.